Identification and characterization of interferon regulatory factor 1 from Lateolabrax japonicus involved in antiviral immune response against grouper nervous necrosis virus infection. Issue 97 (February 2020) - Ma, Zhenhua; Chen, Xu; Yang, Rui; Hu, Jing; Zhou, Shengjie; Yang, Qibing
Abstract: Interferon regulatory factors (IRFs) play a key role in mediating the host response against pathogen infection and other important biological processes. In the present study, an interferon regulation factor 1 gene was identified from Lateolabrax japonicus (designated LjIRF-1 ), the cDNA sequence of LjIRF-1 was 1394 bp long, and with an open reading frame (ORF) of 945 bp that encodes a peptide of 314 amino acids. Bioinformatics data showed that LjIRF-1 possesses a DNA-binding domain (DBD) and two low complexity regions, which shared 56–81% identity to other fish IRF-1s. The LjIRF-1 transcripts were detectable in all examined tissues of healthy L. japonicus, with higher levels in the blood, head-kidney, intestine, gill and spleen. When challenged with grouper nervous necrosis virus (GNNV) and poly (I:C) infection, both the mRNA expression levels of LjIRF-1 and L. japonicus interferon-1 gene (designated LjIFN-1 ) were significantly up-regulated. Furthermore, like with poly (I:C), the active purified recombinant protein (rLjIRF-1) was also capable of increasing the expression level of LjIFN-1 ; controlling the copy number of GNNV under lethiferous titer (10 11 -10 12 copies/μL) and promoting the survival rate of GNNV infected L. japonicas . Combine all the results, we deduced that LjIRF-1 is involved in defending GNNV infection by simulating LjIFN-1 signal pathway in L. japonicas. Highlights: We characterized a interferon regulatory factor 1 from Lateolabrax japonicus. LjIRF-1 and LjIFN-1 can be induced by GNNV and poly (I:C) stimulation. LjIRF-1 can protect L. japonicus against GNNV infections.